A review of Cyrtodiopsis Frey (Diptera, Diopsidae) from China - Liu, Liqun; Wu, Hong; Yang, Ding (Zootaxa, 2009)
The species of the genus Cyrtodiopsis Frey from China are reviewed. Two new species, Cyrtodiopsis pseudoconcava sp. nov. and Cyrtodiopsis yunnanensis sp. nov., are described from China. Two known species, Cyrtodiopsis concava Yang et Chen, 1996 and C. plauta Yang et Chen, 1996, are redescribed. A key to the species of the genus from China is presented.